THE RELATIONSHIP BETWEEN KNOWLEDGE AND ATTITUDES ABOUT REPRODUCTIVE HEALTH AND THE PREVENTION OF SEXUALLY TRANSMITTED INFECTIONS AMONG ADOLESCENTS - Sartika, Maya (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2025)
The number of cases of STIs (sexually transmitted infections) caused by bacteria, viruses, parasites or lice in the genitals and transmitted through sexual intercourse is still relatively high, This is because the public, especially teenagers, do not have adequate understanding of sexually transmitted infections. They have an attitude of curiosity and want to try, but they are not aware of the impact of sexually transmitted infections in the form of health problems. Good knowledge is an important foundation in forming an attitude of avoiding and avoiding free sex. Objective: to be able to increase understanding of reproductive health and prevent the prevention of STIs in teenagers at Baturaja Development Cadre High School. Method: The author uses a descriptive quantitative research method, with a cross-sectional approach. The population in this study was all students who attended Kader Pembangunan Baturaja High School, totaling 82 people, and the sample in this study was 76 respondents who were taken using a purposive sampling technique according to the inclusion and exclusion criteria. Results: After conducting research on 76 respondents, it was found that the results of the Chi Square test obtained a ρ Value of 0.000 < (0.05). This means that there is a relationship between attitudes about reproductive health and the prevention of STIs in teenagers at Baturaja Development Cadre High School. Conclusion: There is a relationship between knowledge and attitudes about reproductive health and the prevention of STIs in teenagers at Baturaja Development Cadre High School.